Passive daytime radiative cooling: from mechanism to materials and applications - Feng, Kai; Wu, Yang; Pei, Xiaowei; Zhou, Feng (Materials today energy, 2024)
In recent years, passive daytime radiative cooling (PDRC) technology has attracted significant attention due to its ability to reflect solar light in the visible near-infrared band (0.3–2.5 μm) and dissipate heat into the universe through the long-wave infrared (LWIR) atmospheric transparency window (8–13 μm). This process is energy-efficient and eco-friendly without any pollution or energy consumption. However, the majority of PDRC materials are subject to intricate preparation procedures, high costs, and limited weather resistance, which impede their practical application. Thus, the optimization of PDRC materials to enhance adaptability and selectivity has become a prominent concern. Despite advancements in the basic theory, material design and application exploration of PDRC, several challenges, such as transparency, durability and intelligent controllability still persist. In this review, the fundamental principles of PDRC technology are summarized and the structure/materials design approaches are highlighted and discussed in detail, and meanwhile, various real-world applications including building cooling, solar cell cooling, personal thermal management, water harvesting, ice and food preservation, and switchable materials are also highlighted. Finally, the challenges and opportunities of PDRC materials are elucidated. This review aims to identify the future development directions and provide guidance for the theoretical exploration, product research and industrialization development of radiative cooling materials. [Display omitted] •The fundamental principles and the structure/materials design approaches for PDRC are discussed in detail.•The real-world applications including building cooling, solar cell cooling, personal thermal management, water harvesting, ice/food preservation and the switchable materials were referred.•The challenges and opportunities of PDRC materials are outlined.